Nanoscience teaching and research program in South Africa - Lindsay, Robert; Nel, Janske (Frontiers in Nanotechnology, 2024)
Since 2012, the National Nanoscience Teaching and Training Platform (NNPTTP), funded by the South African Department of Science and Innovation (DSI), has been responsible for overseeing Africa's first-ever master's in nanoscience program. For over a decade, the NNPTTP has seen the cooperation of four partner universities across South Africa, namely the University of Johannesburg (UJ), University of the Free State (UFS), University of the Western Cape (UWC), and Nelson Mandela University (NMU), culminating in over 250 graduates trained in either nanophysics, nanochemistry, or nanobiology. Originally established to train professionals for a nanotechnologybased industry, both in South Africa and internationally, the program and platform has evolved into a testament to scientific collaboration. This paper discusses the program's framework, successes and challenges, related research, and future plans.